What we owe each other : a new social contract for a better society - Shafik, Minouche (Princeton, New Jersey : Princeton University Press, 2021)
"From one of the leading policy experts of our time, an urgent rethinking of how we can better support each other to thrive. Whether we realize it or not, all of us participate in the social contract every day through mutual obligations among our family, community, place of work, and fellow citizens. Caring for others, paying taxes, and benefiting from public services define the social contract that supports and binds us together as a society. Today, however, our social contract has been broken by changing gender roles, technology, new models of work, aging, and the perils of climate change. Minouche Shafik takes us through stages of life we all experience--raising children, getting educated, falling ill, working, growing old--and shows how a reordering of our societies is possible. Drawing on evidence and examples from around the world, she shows how every country can provide citizens with the basics to have a decent life and be able to contribute to society. But we owe each other more than this. A more generous and inclusive society would also share more risks collectively and ask everyone to contribute for as long as they can so that everyone can fulfill their potential. What We Owe Each Other identifies the key elements of a better social contract that recognizes our interdependencies, supports and invests more in each other, and expects more of individuals in return. Powerful, hopeful, and thought-provoking, What We Owe Each Other provides practical solutions to current challenges and demonstrates how we can build a better society--together"--Publisher's website.
What is the Social Contract? -- Children -- Education -- Health -- Work -- Old age -- Generations -- A new Social Contract.
First published in the United Kingdom by The Bodley Head, an imprint of Vintage, in 2021.
Includes bibliographical references (pages 191-224) and index.
Keywords: Social contract; Social ethics; Public welfare; Human services; Contrat social; Aide sociale; Services sociaux; welfare services; social services; Human services; Public welfare; Social contract; Social ethics